Mechanical and Barrier Properties of Bromo–Butyl Elastomers Filled with Electrochemically Exfoliated Graphene. Issue 8 (29th May 2021) - Verma, Pawan; Zolton, Gabriel C.; Truong, Phuc Vinh; Arole, Kailash; Saha, Sanjit; Sentmanat, Martin L.; Yakovlev, Sergey; Jacob, Sunny; Green, Micah J.; Hule, Rohan A.
Abstract: In this paper, the effects of graphene loading and processing technique on the morphological, mechanical, thermal, rheological, and barrier properties of bromo–butyl rubber, are explored. Bromo–butyl rubber composites with electrochemically exfoliated graphene (EEG) nanosheet filler are prepared via solvent casting and/or melt blending techniques, and their properties are compared against a carbon black control sample. Even though analysis of the EEG composites via microscopy reveals agglomeration problems not present in the carbon black controls, EEG composite samples are observed to have improved barrier properties over carbon black samples in exchange for slightly reduced stress and strain at break. Extensional rheological analysis of the bromo–butyl rubber composites reveals strain hardening phenomena in all the samples and higher extensional modulus in solvent casted‐melt blended (SCM) samples. As a result of better dispersion over the solely melt‐blended samples, the SCM rubber composites exhibit superior tensile modulus and extensional modulus compared to the samples that are solely melt‐blended. Abstract : This paper explores the effects of electrochemically exfoliated graphene (EEG) loading and processing technique on morphological, mechanical, thermal, rheological, and barrier properties of bromo–butyl rubber, comparing EEG against carbon black, and solvent casting‐melt blending (SCM) against melt blending. EEG loading results in improved barrier properties and slightly reduced mechanical properties, while SCM results in superior tensile and extensional moduli.